THE EFFECT OF LEVERAGE, PROFITABILITY AND INFORMATION ASYMMETRY ON EARNINGS MANAGEMENT - Angelina, Gracia; Setijaningsih, Herlin Tundjung (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study was to determine whether leverage, net profit margin, and information assymetry have an influence on earnings management in consumer non cyclical companies listed on the Indonesia Stock Exchange during 2019-2021. Sample were taken by purposive sampling method and had several predetermined criteria. The number of samples that were successfully taken were 61 consumer non cyclicals companies. The data is processed using multiple regression alaysis and EViews 12 software. Based on the result of the research that has been done, it is found that leverage has a negative effect on earnings management, while net profit margin and information asymmetry has no effect on earnings management.